2018
DOI: 10.14336/ad.2017.0924
|View full text |Cite
|
Sign up to set email alerts
|

Pkcδ Activation is Involved in ROS-Mediated Mitochondrial Dysfunction and Apoptosis in Cardiomyocytes Exposed to Advanced Glycation End Products (Ages)

Abstract: Diabetic patients exhibit serum AGE accumulation, which is associated with reactive oxygen species (ROS) production and diabetic cardiomyopathy. ROS-induced PKCδ activation is linked to mitochondrial dysfunction in human cells. However, the role of PKCδ in cardiac and mitochondrial dysfunction caused by AGE in diabetes is still unclear. AGE-BSA-treated cardiac cells showed dose- and time-dependent cell apoptosis, ROS generation, and selective PKCδ activation, which were reversed by NAC and rotenone. Similar te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 61 publications
(83 reference statements)
3
42
0
Order By: Relevance
“…Briefly, AGE was prepared by incubating bovine serum albumin (A8806, BSA, fraction V, fatty acid-free, endotoxin-free; Sigma Chemical, 100 mg/mL) with D-glucose (1 M) in Dulbecco's phosphate-buffered saline (DPBS, 21600-010; Gibco) for 12 weeks at 37 • C. Unmodified BSA was prepared under the same conditions without glucose as a control. The fluorescence of the supernatant was determined (excitation 370 nm, emission 440 nm) using LJL Biosystems (Analyst TM AD, Sunnyvale, CA, USA), which confirmed the higher intensity of AGEs in AGE-modified BSA than in unmodified BSA in our previous paper [21]. The AGE solution was filter sterilized by a 0.8 µM Millex GP filter unit (Millipore, Billerica, MA, USA).…”
Section: Glucose-derived Age Preparationsupporting
confidence: 73%
See 1 more Smart Citation
“…Briefly, AGE was prepared by incubating bovine serum albumin (A8806, BSA, fraction V, fatty acid-free, endotoxin-free; Sigma Chemical, 100 mg/mL) with D-glucose (1 M) in Dulbecco's phosphate-buffered saline (DPBS, 21600-010; Gibco) for 12 weeks at 37 • C. Unmodified BSA was prepared under the same conditions without glucose as a control. The fluorescence of the supernatant was determined (excitation 370 nm, emission 440 nm) using LJL Biosystems (Analyst TM AD, Sunnyvale, CA, USA), which confirmed the higher intensity of AGEs in AGE-modified BSA than in unmodified BSA in our previous paper [21]. The AGE solution was filter sterilized by a 0.8 µM Millex GP filter unit (Millipore, Billerica, MA, USA).…”
Section: Glucose-derived Age Preparationsupporting
confidence: 73%
“…By exploring the effects of DATS on survival markers, we found that DATS treatment increased p-Akt protein levels, indicating that DATS may maintain cardiomyoblast growth and apoptosis inhibition ( Figure 2B). Our prior studies demonstrated that PKCδ activation was involved in ROS-mediated mitochondrial dysfunction and apoptosis in response to AGE exposure [21]. To explore whether DATS could inhibit PKCδ-dependent apoptosis in AGE-exposed H9c2 cells, we performed Western blotting to examine the related proteins.…”
Section: Inhibitory Effect Of Dats On Age-induced Cardiac Apoptosis Amentioning
confidence: 99%
“…All of this agent can cuss increase the reactive oxygen spice (ROS) in cardiomyocytes. An increase in ROS at the cellular level is the start point in beginning apoptosis [33]. In this study although the oxidative stress marker was not measured, however apoptosis marker (caspase 3 and pro-caspase 3) measured and increased with DFO for four weeks.…”
Section: Discussionmentioning
confidence: 62%
“…Increased mitochondrial fission and/or attenuated fusion lead to mitochondrial fragmentation and disrupt cellular physiological function (Caja et al, 2017). Previous studies indicate that the increased mitochondrial fission leads to mitochondrial ROS (mtROS) generation and elevated apoptosis in endothelial cells (ECs) of diabetic patients (Shenouda et al, 2011;Yang et al, 2018;Galloway et al, 2012). Mitochondrial fragmentation, increased expression of the fission factor and reduced fusion protein levels were demonstrated in ECs of type 1 diabetic mice (Makino et al, 2010).…”
Section: Discussionmentioning
confidence: 99%